DRAFT ON MEDIA AS CULTURAL ASPECT: AS THEY SHOW THEMSELVES AND WORK IN COOPERATION WITH EACH OTHER, THEY SHOW THEIR TIME AS SOCIAL ELEMENTS THAT THEY ARE - Martinez, Lis Yana de Lima (Revista Contraponto, 2017)
Intermediality has been the motivation analysis that focused on the different relations between media, as well as their historical evolution within this process of dialogue. Intermedia was the term coined in the mid-sixties by the artist Dick Higgins to describe various interdisciplinary artistic activities that had been taking place. Rajewsky further explains that there are advantages and disadvantages when using a broad definition of the term intermediality. Mixing images to text, unpretentiously, I present this draft, far from being considered a definitive text, in which I bring some media matters, how media relate to each other and how they relate to what is “external” to them, us.